PENGARUH PENGAWASAN DAN MOTIFASI KERJA TERHADAP PENINGKATAN KINERJA PEGAWAI PADA BADAN PENGAWAS KABUPATEN KONAWE - tin, Nar; Irfan Rama, Muhamad (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2019)
This study aims to determine how much influence supervisors and work motivation have on increasing employee work at the Konawe Regency Supervisory Agency. The subjects of this study were employees at the Konawe Regency Supervisory Board. Thus the sample in this study was 56 research population. The research results show that work supervision and motivation together have a positive influence on improving employee performance in the Konawe Regency Supervisory Agency, this is obtained from the results of the management of .F count data, amounting to 670,672 while the magnitude of F Table with free degrees (df) 2 and 53 at cx (0.05) of 3.1504. Thus the value of F count> F table, so the Hypothesis taken Ho is rejected, H1 is accepted. Oversight has a positive influence on the performance improvement of employees in the Konawe Regency Supervisory Agency, this is based on the results of processing obtained values t count is 15,243, while the magnitude of t table with free degree (df) 53 on cx (0,025) is 2,000. Thus the value of t count> table, so the hypothesis taken Ho is rejected, H1 is accepted. Work motivation has a positive effect on improvement employee performance in the Konawe Regency Supervisory Agency, this is based on the results of the management of the data obtained by the value of t hit ung amounted to 13,322, while the magnitude of t table with free degrees (df) 53 at cx (0,025) of 2,000: Thus the value of t count> t table, so the hypothesis taken is Ho rejected, H1 accepted. Obtained Determination Coefficient (R2)) ABOUT 0.962, meaning that 96.2% of the diversity of employee employment increases is caused by a variety of supervision and Work Motivation, while the remaining 3.8% is caused by other factors which are not analyzed further in this study.